2009
DOI: 10.1159/000256652
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimers Predict Stroke Subtype when Assessed Early

Abstract: Background:Early classification of ischemic stroke subtype is important for secondary stroke prevention and may guide further investigations. Methods: Levels of coagulation activation [fibrinopeptide A (FPA), prothrombin fragment 1+2 (F1+2), thrombin-antithrombin complex (TAT)] and fibrinolysis activation [plasmin-α2-antiplasmin complex (PAP), D-dimers] markers were measured in 98 consecutive patients with a first-ever acute ischemic stroke admitted within 12 h after symptom onset. Results: Median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 33 publications
0
24
1
1
Order By: Relevance
“…However, these findings are not direct evidence of cancer-associated hypercoagulation and also seen in cardioembolic stroke. Nevertheless, the cut off D-dimer value of 10.4 µg/mL for hDD in our study was quite higher than D-dimer values observed in cardioembolic stroke [23][24][25]. Also, previous studies have suggested that MVTI was more sensitive to presumed cancer-associated stroke than cardioembolic stroke [1,3,11,[26][27][28].…”
Section: Discussioncontrasting
confidence: 72%
“…However, these findings are not direct evidence of cancer-associated hypercoagulation and also seen in cardioembolic stroke. Nevertheless, the cut off D-dimer value of 10.4 µg/mL for hDD in our study was quite higher than D-dimer values observed in cardioembolic stroke [23][24][25]. Also, previous studies have suggested that MVTI was more sensitive to presumed cancer-associated stroke than cardioembolic stroke [1,3,11,[26][27][28].…”
Section: Discussioncontrasting
confidence: 72%
“…D-Dimer has been associated with cardioembolic stroke in other studies, with Ageno et al reporting a D-Dimer level >2.0 ug/mL to be predictive of cardioembolic stroke with specificity of 93.2% and sensitivity of 59.3% [36,37]. A more recent study confirms these findings [38]. BNP has also been associated with embolism in patients with atrial fibrillation [39,40].…”
Section: Biomarkers Of Ischemic Stroke Etiologymentioning
confidence: 66%
“…The possibility of an increased time window for NT-proBNP measurements is an important possible advantage of the use of NT-proBNP instead of BNP in this setting, as NT-pro BNP is known to have an increased half-life (18). This extended time window of 72 hours can also have an advantage over the user of D-dimers for the diagnosis of cardioembolic stroke, which were found to be potentially useful for the diagnosis of cardioembolic stroke in the first 12 hours after ischemic stroke (19).…”
Section: Discussionmentioning
confidence: 99%